2022
DOI: 10.5455/njcm.20200424065415
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with under nutrition among 6-59 Months Old Children in Rishikesh, Uttarakhand

Abstract: Context: Under nutrition has long been a major public health concern in developing country like India as a leading cause of child morbidity and mortality. The study was aimed to assess the malnutrition and factors associated with it. The study was conducted to assess under nutrition in under five children and various associated factors affecting it. Methodology A community based cross sectional study was conducted among 400 under five children of rural and urban Rishikesh. Multistage sampling method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A study conducted by Chawla et al, 21 in Haryana showed that underweight was significantly associated with birth weight, birth order, prelacteal feed, exclusive breastfeeding, and introduction of complementary feeding while stunting and wasting was significantly associated with birth weight, prelacteal feed, exclusive breastfeeding, and introduction of complementary feeding. A study conducted by Rehan et al, 20 in Rishikesh showed that stunting and wasting were not significantly associated with birth order, birth weight, and immunization status.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A study conducted by Chawla et al, 21 in Haryana showed that underweight was significantly associated with birth weight, birth order, prelacteal feed, exclusive breastfeeding, and introduction of complementary feeding while stunting and wasting was significantly associated with birth weight, prelacteal feed, exclusive breastfeeding, and introduction of complementary feeding. A study conducted by Rehan et al, 20 in Rishikesh showed that stunting and wasting were not significantly associated with birth order, birth weight, and immunization status.…”
Section: Discussionmentioning
confidence: 93%
“…A study conducted by Singh et al, 19 in different districts and found that mother's education is significantly associated with underweight and stunting. A study conducted in Rishikesh, Uttarakhand by Rehan et al, 20 observed that stunting and wasting were statistically significant found with literacy status of family and father's occupation while no statistical significance observed with socioeconomic class and type of family.…”
Section: Discussionmentioning
confidence: 96%